Robust algorithms for the solution of the ideal adsorbed solution theory equations. Issue 3 (24th November 2014) - Mangano, Enzo; Friedrich, Daniel; Brandani, Stefano
<x xml:space="preserve">Abstract</x> The ideal adsorbed solution (IAS) theory has been shown to predict reliably multicomponent adsorption for both gas and liquid systems. There is a lack of understanding of the conditions which guarantee convergence for various algorithms used to solve the IAS theory equations and inconsistencies are present in the reported computational effort required for the different approaches. The original nested loop and the FastIAS technique are revisited. The resulting system of equations is highly nonlinear but both methods are shown to be robust if appropriate choices are made for the starting values of the unknown variables. New initial conditions are proposed and the resulting algorithms are compared in a consistent manner with the main methods available to solve the IAS theory equations. The algorithms are extended for the first time to all nontype I isotherms. © 2014 American Institute of Chemical Engineers AIChE J, 61: 981–991, 2015